Methods, techniques and aI solutions in the age of hostilities. Online hate speech trilogy (vol. 3) (2024)
This is the third book in the Online Hate Speech Trilogy. It focuses on presenting methods for detecting, analysing, and combating toxic language on the Internet. Alongside the legal dilemmas born from a desire to punish hate speech disseminators, identifying online hate speech is one of the biggest challenges in the field of studies on violent narratives and virtual attacks. The authors analyse the challenges of identifying violent narratives through automation, the advantages of manually coding social media posts, and the opportunities offered by AI in this field of research.